The peculiarity of value physical ability of students to take into account the type of body state - Бурень, Н. В.; Потьомкіна, О. І.; Богатко, М. О. (Slobozhanskyi Herald of Science and Sport, 2011)
The work deals with the peculiarity of value physical ability of students to take into account the type of body state. The results of research of the interconnection with the type of body state and physical ability are presented.